Studi Visual Poster Dinas Kesehatan Tebing Tinggi - Rizka Ayu Nindya (LPPM STIKI Malang, 2021)
This study aims to ilustrate the application of elements that affect the design such as the application of text elements , the compatibility of the typeface to the message, the compability of the color with the text, and the visual compatibility of the theme on the 2019 tebing Tinggi health office poster. There are 25 posters of varios kinds on the posters the sample of this research by using purposive sampling, the technique of taking sample with consideration, the researcher took 5 posters as the sample. This research was conducted a descriptive researcher based on direct obsevation and literature study. The resuits showed that all poster was good, obtained through study and interpreted by the outher from the entire poster, they are the application of text element cukup lancar dibaca elemen teks- the application of the typeface is match with the message, the color is match with the text, the visual is suitable with the theme Tebing Tinggi health office poster in 2019 can be concluded as in good category.